ANALISIS KEUNTUNGAN USAHATANI PADI SAWAH PASCA TAMBANG EMAS DI DESA WUMBUBANGKA KECAMATAN RAROWATU UTARA - Rustam Supendy (Universitas Tadulako, 2016)
The purpose of this research was to analyze the profit of wetlend rice farming system in Wumbubangka village Rarowatu sub district of Bombana district. This research conducted from January until Mei 2015. The samples in this research were takenusing a random sampling method. Population of the samples was 50 people. Data was analyzed using profit analysis of farming system such as ∏ = TR – TC = P. Q – TFC –TVC, and B/C ratio. The results of the research showed that the profit of the wetland rice farming in farming in Wumbubangka village Rarowatu sub district of Bombana district was IDR 3,848,750 with the B/C valuewas 2.89. Key words : Farming System, B/C ratio, Wetland rice.